Teori Ras Kritis: Sebuah Contoh Konsep Keadilan Sosial Yang Asing Menurut Alkitab - Kalvin S. Budiman (Veritas : Jurnal Teologi dan Pelayanan, 2022)
Not all social justice teachings are social justice according to the teaching of the Bible. The case in point is the teaching of critical theory on racism (Critical Race Theory or CRT). This teaching that nowadays has a strong influence over universities in the United States promotes widely concepts such as systemic racism, social binary, and intersectionality, which has actually caused a social rift marked by never-ending racial prejudice. From the biblical point of view, the critical theory view of racism contains social consequences that harm society at large. It has taught a social mindset that runs counter to the biblical teachings on social justice. After discussing the historical background of CRT and the basic tenets of CRT, I will then provide an evaluation of CRT from the biblical perspective by observing its starting point, its view of the root cause of racism, and the primary solution that it offers.